Pharmaceutical care for patients with hepatic diseases - Silva, Adriana Ramazzoti Chanan; Borin, Fabiane Yuri Yamacita; Vivan, Rosália Hernandes Fernandes (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Farmácia, 2022)
The indiscriminate consumption of over-the-counter medications has caused a significant increase in cases of liver poisoning. In Brazil, the SINITOX (Mexico-National Pharmacological Information System) reported that 36.05% of poisoning cases were caused by drugs. An overload of metabolised drugs in the liver can cause hepatotoxicity and lead to liver damage. In order to avoid the indiscriminate use of these drugs and the occurrence of adverse damages, the role of the pharmaceutical professional in the assessment of patient prescriptions and guidelines is important. Pharmaceutical care plays a fundamental role in pharmacotherapy, in order to improve the patient's quality of life, minimizing how it reduces adverse effects and reduces treatment incidence and adherence. It is crucial that the pharmaceutical professional impose himself and not just be a drug salesman. In this sense, the present work aims to highlight the importance of Pharmaceutical Care to monitor the patient and reduce the effects and possible injuries caused by hepatotoxic drugs. To carry out the research, a literature review was conducted on the theme Pharmaceutical Care, in the pharmacological treatment with hepatotoxic drugs through books, electronic data, texts and articles from 1999 to 2019.